81a2 + 36a + 4

Question

Asked 1/12/2015 10:42:13 AM

Updated 1/12/2015 11:45:51 AM

1 Answer/Comment

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [1/12/2015 11:46:10 AM]

s

Question

Asked 1/12/2015 10:42:13 AM

Updated 1/12/2015 11:45:51 AM

1 Answer/Comment

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [1/12/2015 11:46:10 AM]

Rating

3

n^2 + 7n - 44 = (n - 4)(n + 11)

Added 1/12/2015 11:45:51 AM

This answer has been confirmed as correct and helpful.

Identify the polynomial.
a 2 b - cd 3 **Weegy:** The polynomial a^2b - cd^3 is a binomial (two-term polynomial). **User:** (y 4 - 1) ÷ (y + 1) **User:** Perform the indicated operation.
(y 4 - 1) ÷ (y + 1) **User:** Factor k2 - 81. (More)

Question

Not Answered

Updated 1/26/2015 10:23:34 PM

2 Answers/Comments

(y^4 - 1) ÷ (y + 1)

= (y^2 + 1)(y + 1)(y - 1)/(y + 1)

= (y^2 + 1)(y - 1)

= y^3 - y^2 + y - 1

= (y^2 + 1)(y + 1)(y - 1)/(y + 1)

= (y^2 + 1)(y - 1)

= y^3 - y^2 + y - 1

Added 1/26/2015 10:23:13 PM

This answer has been confirmed as correct and helpful.

Confirmed by Andrew. [1/27/2015 3:42:26 AM]

Find the greatest common factor of -30x 4 yz 3 and 75x 4 z 2. **Weegy:** The greatest common factor of -30x^4 yz^3 and 75x^4 z^2 is 15x^4z^2 **User:** What is the middle product of (-2x + 1)(-3x - 5) (More)

Question

Not Answered

Updated 1/16/2015 2:19:05 AM

2 Answers/Comments

The middle product of (-2x + 1)(-3x - 5) is 7x .

(-2x + 1)(-3x - 5)

= -2x*(-3x) - 3x + (-2x)*(-5) - 5

= 6x^2 - 3x + 10x - 5

= 6x^2 + 7x - 5

(-2x + 1)(-3x - 5)

= -2x*(-3x) - 3x + (-2x)*(-5) - 5

= 6x^2 - 3x + 10x - 5

= 6x^2 + 7x - 5

Added 1/16/2015 2:19:05 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [1/16/2015 3:35:23 AM]

x 4 + 7 by x - 3 User: a 3 b 2 · 4ab 3 User: p 2 - 8p - 20

Question

Not Answered

Updated 1/18/2015 10:01:42 PM

1 Answer/Comment

a - b + c, b - c + d, and c - d + e User: Factor k 2 - 17k + 16. User: Factor 9b 2 - 4. User: Factor the following polynomial completely.
-x 2 y 2 + x 4 + 9y 2 - 9x 2 User: Factor the four-term polynomial.
pq - 3r + pr - 3q. User: Find the sum and choose the correct answer.
2n 3 + 4n 2 - 7 and -n 3 + 8n - 9 **Weegy:** Can you provide us the options and clarify the equation given please. **User:** 2n 3 + 4n 2 - 7 and -n 3 + 8n - 9 **User:** Select the correct difference.
5d 2 + 4d - 3 less 2d 2 - 3d + 4 (More)

Question

Not Answered

Updated 1/15/2015 4:56:48 AM

2 Answers/Comments

(a - b + c) + (b - c + d) + (c - d + e)

= a - b + c + b - c + d + c - d + e

= a + c - c + c + d - d + e

= a + c + e

= a - b + c + b - c + d + c - d + e

= a + c - c + c + d - d + e

= a + c + e

Added 1/15/2015 4:55:15 AM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [1/16/2015 1:19:17 PM]

5d^2 + 4d - 3 - (2d^2 - 3d + 4)

= 5d^2 + 4d - 3 - 2d^2 + 3d - 4

= 3d^2 + 7d - 7

= 5d^2 + 4d - 3 - 2d^2 + 3d - 4

= 3d^2 + 7d - 7

Added 1/15/2015 4:56:47 AM

Simplify the expression.
2(3y - 7) - 5y(2 - y) **Weegy:** 2(3y - 7) - 5y(2 - y) = 6y - 14 - 10y + 5y^2 = 5y^2 - 4y - 14 **User:** Find the quotient.
42j 4 k 2 ÷ (-3j 3 k) **User:** Find the quotient.
(6x 2 - x - 40) ÷ (5 + 2x) **User:** Factor 360t + 10t 3 - 120t 2 **User:** How many terms are in the polynomial abcd + e - fg + h 2 **Weegy:** There are 4 terms in the polynomial: abcd + e - fg + h^2 **User:** Factor 6x 2 - 17x + 5 **User:** Find the quotient.
(5ab - 10b 2 + 15bc) ÷ 5b **User:** Factor 25x 2 + 10x + 1 **Weegy:** 25x^2+10x+1 = (5x + 1)? **User:** Simplify m - {n + [p - (m + n - p)]}. **Weegy:** 5 + 2{x - 4[3x + 7(2 - x)]} = 5 + 2{x - 4[3x + 14 - 7x]} = 5 + 2{x - 4[-4x + 14]} = 5 + 2{x + 16x - 56} = 5 + 2{17x - 56} = 5 + 34x - 112 = 34x - 107 **User:** Choose the product.
(5x 2 + 2x - 3)(x - 1) **User:** Factor 3x 2 - 15x - 42. **Weegy:** 4. 3(x - 7)(x + 2) is the answer. 3x^2 - 15x - 42 = 3(x - 7)(x + 2) **User:** Find the product.
(n + 8)(n - 2) **Weegy:** (25x^2 + 20xy + 16y^2)(5x - 4y) = 125x^3 - 64y^3 **User:** Choose the product.
-7p 3(4p 2 + 3p - 1) **Weegy:** -7p^3(4p^2 + 3p - 1) = -28p^5 - 21p^4 + 7p^3 **User:** Factor k 2 + 13k + 12 **User:** Factor -2bk 2 + 6bk - 2b. **User:** Select the correct difference.
-3z 7 - (-5z 7) **Weegy:** -3z^(7)-(-5z^(7))
Multiply -1 by the -5z^(7) inside the parentheses.
-3z^(7)-1*-5z^(7)
Multiply -1 by -5z^(7) to get 5z^(7).
-3z^(7)+5z^(7)
According to the distributive property, for any numbers a, b, and c, a(b+c)=ab+ac and (b+c)a=ba+ca. [ Here, z^(7) is a factor of both -3z^(7) and 5z^(7).
(-3+5)z^(7)
To add integers with different signs, subtract their absolute values and give the result the same sign as the integer with the greater absolute value. In this example, subtract the absolute values of -3 and 5 and give the result the same sign as the integer with the greater absolute value.
(2)z^(7)
Remove the parentheses.
2z^(7) ] **User:** Find the greatest common factor of 15x 2 y 3 and -18x 3 yz. (More)

Question

Updated 1/14/2015 7:33:10 PM

2 Answers/Comments

m - {n + [p - (m + n - p)]}

= m - {n + (p - m - n + p)}

= m - {n + 2p - m - n }

= m - (2p - m)

= m + m - 2p

= 2m - 2p

= m - {n + (p - m - n + p)}

= m - {n + 2p - m - n }

= m - (2p - m)

= m + m - 2p

= 2m - 2p

Added 1/14/2015 7:31:58 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [1/15/2015 5:50:53 AM]

(n + 8)(n - 2)

= n*n + 8*n - 2*n - 8*2

= n^2 + 8n - 2n - 16

= n^2 + 6n - 16

= n*n + 8*n - 2*n - 8*2

= n^2 + 8n - 2n - 16

= n^2 + 6n - 16

Added 1/14/2015 7:32:36 PM

31,097,189

questions answered

victoria3

$107.11

Hearts 2,186 Views 8,712 Streams 112

PranaMachine

$80.97

Hearts 1,653 Views 6,405 Streams 87

phpmicro

$66.25

Hearts 1,340 Views 136,589 Streams 116

jezziem

$33.60

Hearts 805 Views 47,131 Streams 45

judymrnd

$21.15

Hearts 549 Views 32,158 Streams 36

wallet.ro

$16.70

Hearts 366 Views 10,862 Streams 17

sacharyn

$12.15

Hearts 364 Views 16,451 Streams 22

emdjay23

$11.50

Hearts 820 Views 39,620 Streams 56

There are no comments.